THE INFLUENCE OF EMPLOYEE COMPETENCE AND INTERNAL CONTROL SYSTEM ON THE QUALITY OF LOCAL GOVERNMENT ACCOUNTING INFORMATION IN WEST JAVA REGION - Pangestika, Nasilem; Ahmadi, Agus Khairudin (Soedirman Accounting, Auditing and Public Sector Journal, 2024)
This study aims to analyze the effect of the internal control system on the quality of financial statements at the West Java Regional Financial Management Office. The results showed that the internal control system in the control environment has a significant positive effect on the quality of financial statements, with a significance value of 0.004 and a t-count of 3.155 which is greater than the t-table of 1.703. This indicates that the effective implementation of the internal control system can improve the quality of financial statements. However, the preparation and implementation of policies related to human resource development still need to be improved. In addition, the internal control system in risk assessment also has a positive effect with a significance value of 0.013 and a t-count of 2.110, indicating that risk identification needs to be done with a more comprehensive methodology. Simultaneously, both the control environment and risk assessment have a significant effect on the quality of financial statements with a significance value of 0.009 and an F-count of 5.717. These findings confirm the importance of strengthening the internal control system to improve the accountability and transparency of local government financial reports.